2014
DOI: 10.1186/1471-2180-14-109
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocin-encoding genes and ExPEC virulence determinants are associated in human fecal Escherichia coli strains

Abstract: BackgroundA set of 1181 E. coli strains of human fecal origin isolated in the South Moravia region of the Czech Republic was collected during the years 2007–2010. Altogether, 17 virulence determinants and 31 bacteriocin-encoding genes were tested in each of them.ResultsThe occurrence of bacteriocin-encoding genes was found to be positively correlated with the occurrence of E. coli virulence factors. Based on the presence of virulence factors and their combinations, E. coli strains were classified as non-pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
59
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 54 publications
6
59
0
3
Order By: Relevance
“…Significant association (p-value 0.006) was found between fimH gene and gender; this association may be due to difference in anatomical structure of urinary tract between male and female (Hickling et al, 2015). The results confirmed the existence of aer gene with more prevalence in diarrheal isolates, this finding totally agreed with Oswald et al (1991), who found that aer gene was positive in 70% of diarrheal samples and Micenková et al (2014) who found aer gene was positive in 68%. High frequency of aer gene in diarrheal isolates may be attributed to the deficiency of iron concentration within gastrointestinal tract, while iron is responsible for microbial metabolism.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Significant association (p-value 0.006) was found between fimH gene and gender; this association may be due to difference in anatomical structure of urinary tract between male and female (Hickling et al, 2015). The results confirmed the existence of aer gene with more prevalence in diarrheal isolates, this finding totally agreed with Oswald et al (1991), who found that aer gene was positive in 70% of diarrheal samples and Micenková et al (2014) who found aer gene was positive in 68%. High frequency of aer gene in diarrheal isolates may be attributed to the deficiency of iron concentration within gastrointestinal tract, while iron is responsible for microbial metabolism.…”
Section: Discussionsupporting
confidence: 82%
“…Prevalence of aerobactin, which confers the ability to bind iron among isolates, was similar to those reported by other investigators in diarrhea isolates. The result show 64% aer gene positive in 50 diarrhea isolates and this percentage is near to other researches (Oswald et al, 1991) result of 70% aer gene positive and Micenková et al (2014) result is 68% aer gene positive.…”
Section: Discussionsupporting
confidence: 72%
“…Usually, E. coli isolates can be classified into commensal, intestinal pathogenic, and extraintestinal pathogenic E. coli (ExPEC) groups, based on different virulence genes [2]. ExPEC usually possesses diverse virulence genes responsible for pathogenesis outside the gastrointestinal tract, and is also distinguished from commensal E. coli by the presence of a broad spectrum of virulence genes [3][4][5], while commensal isolates can also develop into intestinal or ExPEC isolates by acquiring virulence genes [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Further confounding these issues studies like Micenkova et al 's 11 from 2014 demonstrate that bacteriocin-encoding genes and ExPEC VFs are associated in human samples. Using data from both virulence determinants and bacteriocin encoding genes it was determined that these factors correlate positively in E.coli strains of human fecal origin.…”
mentioning
confidence: 99%